Hak Mewaris Laki-Laki Nyeburin Setelah Perceraian di Desa Adat Abiansemal - Maruti, Komang Arya Mukti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 1 (2024), 2024)
The purpose of this study was to analyze the inheritance rights of men who bury themselves after a divorce in the Abiansemal Traditional Village. The research method used is an empirical research method. The results of the study show that the position of men who are buried after a divorce in the family of origin in the Abiansemal Traditional Village and how the position of inheritance rights for men with mulih teruna status in the Abiansemal Traditional Village are given status certainty to these men to return to their original family as family. After status, obligations (swadharma) and rights (swadikara) will appear, bearing in mind that swadharma and swadikara are related to one's position in society, in the form of family fathers and village fathers in accordance with the provisions of the awig-awig/perarem of their customary village. With respect to the obligations (swadharma) and rights (swadikara) for men to bury after a divorce in their original family who return at a young age, where their parents are still alive and other relatives, both brothers and sisters or sisters, are not yet married, that they receive rights and obligations that should be obtained. Furthermore, based on this, the procedures related to the inheritance rights of the men's nyeburin must simply be discussed and resolved within the family of the family concerned. The inheritance process is an internal process desired by the heirs, so that it should be completed internally or involve the family based on the principle of kinship. Tujuan penelitian ini dilakukan untuk menganalisis terkait dengan hak mewaris laki-laki nyeburin setelah perceraian di Desa Adat Abiansemal. Metode penelitian yang digunakan adalah metode penelitian empiris. Hasil penelitian menunjukkan bahwa kedudukan laki-laki nyeburin setelah perceraian dalam keluarga asal pada Desa Adat Abiansemal serta bagaimana kedudukan hak waris bagi laki-laki yang berstatus mulih teruna pada Desa Adat Abiansemal diberikan kepastian status kepada laki-laki tersebut untuk kembali ke keluarga asalnya sebagai keluarga. Setelah status kemudian akan muncul beban kewajiban (swadharma) dan hak (swadikara), mengingat swadharma dan swadikara berhubungan dengan kedudukan seseorang di masyarakat, berupa ayahan keluarga dan ayahan desa sesuai dengan ketentuan awig-awig/perarem desa adatnya. Terhadap kewajiban (swadharma) dan hak (swadikara) kepada laki-laki nyeburin setelah perceraian dalam keluarga asalnya yang kembali pada usia muda, dimana orang tua masih hidup dan saudara yang lain baik kakak ataupun adik laki-laki ataupun perempuan belum menikah bahwa mereka menerima hak dan kewajiban yang seharusnya didapatkannya. Selanjutnya berdasarkan hal tersebut kemudian prosedur yang berkaitan dengan hak waris dari laki-laki nyeburin tersebut secara sederhana harus dibahas dan diselesaikan secara kekeluargaan dari keluarga yang bersangkutan. Proses pewarisan merupakan proses internal yang dikehendaki oleh para ahli waris, sehingga sewajarnya diselesaikan secara internal atau